2019
DOI: 10.1016/j.joca.2019.02.584
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood derived stem cells in OA knee at low resource setting: a phase II RCT

Abstract: validity of current animal studies, high quality experimental studies and efforts for effective translation from preclinical studies to clinical trials are still required. The present study also demonstrates that moderate confidence could be placed in safety of MSCs therapy for knee OA but with low confidence in efficacy outcomes due to limitations of the current evidence. Further high-quality studies with high internal and external validity are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Nineteen studies including 584 knee OA patients (352 cases for MSC group and 232 cases for control group) fulfilled the predefined inclusion criteria and were included in the final analysis ( Figure 1 ). Eighteen publications were full-text articles [ [2] , [3] , [4] , [5] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , 21 , 23 ], and one publication was conference abstract [ 6 ].
Figure 1 Flow diagram of studies identified, included and excluded.
…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies including 584 knee OA patients (352 cases for MSC group and 232 cases for control group) fulfilled the predefined inclusion criteria and were included in the final analysis ( Figure 1 ). Eighteen publications were full-text articles [ [2] , [3] , [4] , [5] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , 21 , 23 ], and one publication was conference abstract [ 6 ].
Figure 1 Flow diagram of studies identified, included and excluded.
…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The characteristics of included studies are shown in Table 1 . Among the included studies, there were 15 RCTs [ 3 , 5 , 6 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , 18 , 19 , 21 , 23 ], two retrospective studies [ 1 , 17 ] and two cohort studies [ 4 , 16 ]. All the 19 papers were fully published during the period from 2012 to 2019.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review article established the use of PBMSCs in cartilage repair and regeneration to be very safe and efficacious (94). In phase II clinical trial on the use of PBSCs in an arthritic knee, it was found that these cells increase the mean cartilage thickness and improve the quality of life (95).…”
Section: Peripheral Blood Derived Mscs (Pb-mscs)mentioning
confidence: 99%